Assessement of architecture design studios using Rasch measurement model - Utaberta, Nangkula; Hassanpour, Badiossadat; Che Ani, Adi Irfan; Mohd Tawil, Norgainy (Fakulti Kejuruteraan dan Alam Bina, UKM, 2012)
Architecture as a multidisciplinary filed has a close relation with other fields like art and because of this nature, its education system is completely different with scientific majors. Students expose themselves to critique and evaluation in each session and in this way by gaining experience they try to upgrade their problem solving skills. Definitely such an education system needs different evaluation and assessment model. Essentially different models and methods are currently implementing in universities and architecture departments all around the world with minimum variations. Unfortunately, despite of its considerable, minimum studies have been conducted and reported in literature. So in order to promote an open discussion and improve the assessment in architecture education, rasch measurement model and mini facet software have been used for the first time to assess the evaluation system at the current architecture studio. This research has been choosing Malaysia (as a model of developing multicultural country) for the study and select Universiti Kebangsaan Malaysia especially architecture department as case study.